SISTEM PEMBAYARAN RINCIAN BIAYA KULIAH PADA PERGURUAN TINGGI RAHARJA MENGGUNAKAN GO+ - Ageng Setiani Rafika; Deviana Ika Putri; Siskawati Sanusi (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2017)
Along with the development of increasingly sophisticated digital technology, online payment system rife used both government and private agencies. Similarly, in Higher Education. Financial Accounting System on Higher Education Prog is called GO (Green orchesta) is said to be still using the method of effective and efficient because students are required to come to campus first to find out some of the bills that must be paid. Even to know RBR (details Registration Fees) and Yandex (details Tuition) still use the local network that can only be accessed on BoxSiS (Student iLearning Service Box). With the rapid development of existing technologies, systems GO (Green orchesta) need to be made updates to the onlineversions are able to be accessed anytime and anywhere by students. Hence comes the system that has been updated is GO + (Green Orchestra Plus). GO + (Green Orchestra Plus), enables all payment systems pekuliahan student as the student can check the details of tuition anywhere and anytime. Not hasrus come kekampus and queued at the box sis. GO + (Green Orchestra Plus) highly efficient and effective for use as it can support the process online payments.